Barreiras à prática de atividades físicas em pacientes portadores de HIV/AIDS atendidos em um serviço de referência do RS - Behenck, Mauri Schwanck (2016)
Regular physical activity is stimulated in HIV/AIDS patients (HIVP) as part of an approach to improve wellbeing and health, however adherence to a routine of daily exercise is low in this population. The purpose of this study was to analyze the personal and environmental barriers to physical activity of HIVP, of both sexes, treated at a reference service for the population of Santa Maria / RS and its relations with individual characteristics and pathology aspects. One hundred and thirty seven patients (90 men and 47 women) were evaluated, aged 40.49 ± 13.73. As instruments for data collection, the questionnaire of personal and environmental barriers to physical activity from Martins and Petroski (2000), the socio-demographic survey of the Brazilian Association of Population Studies (2005) and the International Physical Activity Questionnaire (IPAQ)-short version were used. Anthropometric measurements and relevant information on HIV status were also collected. The barriers for physical activity mostly cited were the personal ones ("long working hours" and "lack of interest in practice"). When considering the subgroups, the "long working hours" barrier was the most present in men, and among individuals considered sufficiently active, individuals who had BMI below 25 kg/m2 and persons in the highest categories of socioeconomic status. On the other hand, the "lack of interest in practice" was the most perceived barrier in women, among individuals considered insufficiently active, those who had a BMI ≥ 25 kg/m2 and users of antiretroviral drugs. No significant correlation was observed between the level of barriers perception and the studied variables. It was concluded that personal barriers were more important than the environmental ones and that the level of perception of personal and environmental barriers to physical activity (total score) indicated by HIVP had no relation to individual characteristics such as sex, age, educational level, socioeconomic status and nutritional status, as well as with aspects related to the disease, such as time of diagnosis, use of antiretroviral drugs, recognition of HIV status among the social group and acceptance/assimilation of this condition.